On the Psychology of Argument: A Structural Analysis of Former Muslims' Postings Within Malaysian Social Media - Hashmi, Umair Munir; Rashid, Radzuwan Ab; Munir, Rabia (Frontiers in Psychology, 2021)
This research attempts to provide insights into the argumentation structures in the discussion of Islam on social media involving 14 Malaysian former Muslims. The participants’ social media accounts were observed for 12 months, from January to December 2019. A total of 368 postings put forth arguments related to Islamic authoritative discourse, the Quran and ‘Sunnah’ of the Prophet Muhammad, to justify their renunciation of the Muslim religion. Toulmin’s (1958) model of argument and Erduran et al. (2004) levels of argument were synthesized as the analytical lens to analyse the arguments given. The analysis revealed that Level 2 argument, which includes the claim, data to support the claim, and the warrant, was identified as the most common argument structure. Level 5, which has more than one rebuttal, was the least common argument structure. The analysis shows that most argument structures were at the lower levels (1 to 3) in that they offered no strong, clearly identifiable rebuttals. This study concludes that the arguments put forth by former Muslims, in the main, are loosely constructed rather than attempts to build a strong cumulative argumentation to support their reasons for abandoning the Muslim faith.